P.S. 1 Italian Bureau selections 1998-2000. - Baciocco, Giovanna; Bertola, Chiara; Cherubini, Laura; Christov-Bakargiev, Carolyn; Codognato, Mario; Gropello, Giulio di; Heiss, Alanna; Melandri, Giovanna; Pistoletto, Michelangelo (Roma : Castelvecchi Arte, 2000)
Bartolini, Massimo ; Berti, Simone ; Es, Brigata ; Esposito, Bruna ; Fantin, Emilio ; Favaretto, Lara ; Marisaldi, Eva ; Mezzaqui, Sabrina ; Norese, Giancarlo ; Pagliarini, Arpiani ; Pivi, Paola ; Rossi, Sara ; Tesi, Alessandra ; Toderi, Grazia ; Torelli, Sabrina ; Vitone, Luca
Engels & Italiaans
P.S. 1 Italian Bureau selections 1998-2000, P.S. 1 Italian Bureau, Roma, 2000
boek
Keywords: Italië